2014
DOI: 10.3389/fpsyt.2014.00071
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics, Stress, and Their Potential Impact on Brain Network Function: A Focus on the Schizophrenia Diatheses

Abstract: The recent sociodevelopmental cognitive model of schizophrenia/psychosis is a highly influential and compelling compendium of research findings. Here, we present logical extensions to this model incorporating ideas drawn from epigenetic mediation of psychiatric disease, and the plausible effects of epigenetics on the emergence of brain network function and dysfunction in adolescence. We discuss how gene–environment interactions, effected by epigenetic mechanisms, might in particular mediate the stress response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 156 publications
0
8
0
1
Order By: Relevance
“…Development or expression of immobility in FSt is disrupted by proximal stress experiences ( Molina et al, 1994 ; Alcaro et al, 2002 ; Becker et al, 2008 ; Mozhui et al, 2010 ), an observation that further support the translational value of this animal model because proximal adverse experiences contribute to development of mental diseases ( Dias-Ferreira et al, 2009 ; Daskalakis et al, 2013 ; Gourley et al, 2013 ; Diwadkar et al, 2014 ; Reul, 2014 ; Eagle et al, 2015 ). The neurobiological mechanisms mediating the disruptive effects of proximal stress experiences on subsequent coping with FSt are still poorly understood, although disturbances of learning processes could play a major role ( Mitchell and Meaney, 1991 ; Colelli et al, 2014 ; Reul, 2014 ).…”
Section: Introductionmentioning
confidence: 61%
“…Development or expression of immobility in FSt is disrupted by proximal stress experiences ( Molina et al, 1994 ; Alcaro et al, 2002 ; Becker et al, 2008 ; Mozhui et al, 2010 ), an observation that further support the translational value of this animal model because proximal adverse experiences contribute to development of mental diseases ( Dias-Ferreira et al, 2009 ; Daskalakis et al, 2013 ; Gourley et al, 2013 ; Diwadkar et al, 2014 ; Reul, 2014 ; Eagle et al, 2015 ). The neurobiological mechanisms mediating the disruptive effects of proximal stress experiences on subsequent coping with FSt are still poorly understood, although disturbances of learning processes could play a major role ( Mitchell and Meaney, 1991 ; Colelli et al, 2014 ; Reul, 2014 ).…”
Section: Introductionmentioning
confidence: 61%
“…4 ). For instance, stress-induced epigenetic changes, either during perinatal and/or adolescent stages of development ( McGowan and Szyf, 2010 , Chakraverty et al., 2014 , Lo and Zhou, 2014 , Diwadkar et al., 2014 ), will need to be examined and whether these alterations in the individual's epigenetic landscape are context- or germline-dependent ( Crews, 2008 ). Furthermore, future experiments will need to investigate sex differences in these potential mechanisms mediating stress resilience, given the significant role of sex in modulating responsiveness to stressors ( Becker et al., 2007 , Bangasser and Valentino, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that early life stress may result in microstructural hippocampal changes such as reduced neurogenesis and dendritogenesis [ 48 ], leading to reduced hippocampal volumes [ 20 ]. Early life adversity is thought to interact with inherent genetic vulnerabilities resulting in hippocampal morphological changes and dysfunctional information processing [ 14 ]. The hippocampus is the major hub integrating memory and emotion and dispersing information throughout the limbic system to and from the amygdala, thalamic, cingulate, and frontal regions [ 44 , 47 , 57 ].…”
Section: Introductionmentioning
confidence: 99%